Аналіз програмних продуктів для забезпечення процесу дистанційної освіти - Mochalov, О. О.; Gaysha, О. О. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2017)
The software to be used in distance education has been analyzed. Means for studies and control of this process are considered. Possible disturbances in the distance education are discussed and techniques for their neutralization are pointed to.